2022
DOI: 10.3390/d14030157
|View full text |Cite
|
Sign up to set email alerts
|

Phylotranscriptomic and Evolutionary Analyses of Oedogoniales (Chlorophyceae, Chlorophyta)

Abstract: This study determined the transcriptomes of eight Oedogoniales species, including six species from Oedogonium and two species from Oedocladium to conduct phylotranscriptomic and evolutionary analyses. 155,952 gene families and 192 single-copy orthogroups were detected. Phylotranscriptomic analyses based on single-copy orthogroups were conducted using supermatrix and coalescent-based approaches. The phylotranscriptomic analysis results revealed that Oedogonium is polyphyletic, and Oedocladium clustered with Oed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Due to its distinct benefits, phylotranscriptomics is increasingly being used for phylogenetic and evolutionary investigations on green algae. It has been demonstrated that acquiring high-density transcriptomic data in conjunction with the development of numerous sophisticated analytical techniques is an effective strategy for clarifying ambiguous evolutionary relationships between distinct species [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. However, no transcriptomic data had been published on members of the Chaetophorales and little was known about the phylotranscriptomics of this order.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its distinct benefits, phylotranscriptomics is increasingly being used for phylogenetic and evolutionary investigations on green algae. It has been demonstrated that acquiring high-density transcriptomic data in conjunction with the development of numerous sophisticated analytical techniques is an effective strategy for clarifying ambiguous evolutionary relationships between distinct species [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. However, no transcriptomic data had been published on members of the Chaetophorales and little was known about the phylotranscriptomics of this order.…”
Section: Introductionmentioning
confidence: 99%